Synthesis of amino-functionalized mesoporous silica sheets and their application for metal ion capture - Kazuma Nakanishi (Journal of Asian Ceramic Societies, 2015)
Novel mesoporous silica sheets with surface amino-functional groups (sheet-NH2) were prepared for the efficient adsorption of aqueous metal ions. The sheet-NH2 were synthesized by a dual-templating process using Pluronic P123 and N-palmitoyl-l-alanine as templates. Two silicone regents were used to form the silica framework: tetraethoxysilane and 3-aminopropyltriethoxysilane. In the synthetic process, the as-prepared silicate was refluxed in ethanol to remove the organic templates remaining from the surface amino groups derived from APTES. The prepared sheet-NH2 showed widths of several micrometres and small thicknesses of approximately 50 nm. The pore diameter, pore volume and BET surface area of sheet-NH2 were determined by nitrogen adsorption–desorption isotherms to be 3.1 nm, 0.73 cm3 g−1 and 189.9 m2 g−1, respectively. TEM, XRD, FT-IR and TG–DTA analysis demonstrated that the sheet material had a disordered mesoporous structure and contained organic chains. The adsorptions of aqueous zinc(II) and copper(II) metal ions were examined and compared with amino-functionalized conventional mesoporous silica (MCM-NH2), calcined mesoporous silica sheets and silica beads with no porous structures. Notably, the sheet-NH2 exhibited the highest adsorption of both zinc and copper ions among the examined materials. In addition, the metal ion sorption equilibrium data of sheet-NH2 were fitted to the Langmuir isotherm model.